1984
DOI: 10.1016/0035-9203(84)90272-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with killed Acanthamoeba culbertsoni antigen and amoeba culture supernatant antigen in experimental Acanthamoeba meningoencephalitis

Abstract: Mice immunized with killed (sonicated) Acanthamoeba culbertsoni A-1 antigen displayed marked resistance to intranasal challenge with the amoeba. A primary immunization produced a survival rate of approximately 40%, and survival values of greater than 80% were obtained by multiple immunizations. Similarly mice immunized with fluids from A-1 cultures were highly resistant to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Mouse macrophages activated with lymphokines also display amoebicidal properties for N . fowleri (Ferrante 1984). This non-specific immunity may explain the findings that mice treated with agents known to be macrophage activators, e.g., Salmonella enteritidis 1 1 RX or muramyl dipeptide, are resistant to N .…”
Section: Parameters Of Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mouse macrophages activated with lymphokines also display amoebicidal properties for N . fowleri (Ferrante 1984). This non-specific immunity may explain the findings that mice treated with agents known to be macrophage activators, e.g., Salmonella enteritidis 1 1 RX or muramyl dipeptide, are resistant to N .…”
Section: Parameters Of Infectionmentioning
confidence: 99%
“…Studies in mice have demonstrated that it is possible to immunize animals against Acanthamoeba meningoencephalitis (Culbertson 1971, Rowan-Kelly & Ferrante 1984. Animals immunized intraperitoneally with sonicated trophozoites of A .…”
Section: Immunity In Experimental Amoebic Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy is believed to depend on dierences in the immunity mechanisms between these two amoebae (Ferrante 1991). Anti-Acanthamoeba antibodies apparently block the cytopathic eect of acanthamoebae (Cursons et al 1980a) and highly eective protection against Acanthamoeba meningoencephalitis after immunisation with Acanthamoeba antigen has repeatedly been demonstrated in animal models (Culbertson 1971;Rowan-Kelly and Ferrante 1984). It is unknown, however, whether the immunological status of the patient is also somehow important for the establishment of an Acanthamoeba keratitis.…”
Section: Introductionmentioning
confidence: 99%